Treasures from a time capsule of the Chinese Empire Reform Association, 1905 [03] - Yang, Charles (2022)
A photograph of a jade Buddha - one of the items placed into the time capsule of the association's new headquarters at 1715 Government Street in 1905, and discovered by the owner of the building during recent renovations.